Pengembangan Aplikasi Edukasi Grammar Berbasis Web dengan Penerapan UX Design dan Gamifikasi Melalui Pendekatan Agile Development - Andhik Ampuh Yunanto; Irwan Sumarsono; Sylvi Indryana Safira (Teknik Informatika Universitas Pamulang, 2023)
In today's technological developments, there are many applications and systems that have been used by the community, both children and adults. This impact causes the technological era to continue to develop rapidly so that the existence of applications has become a basic need for the community. One of the emerging technologies today is an application that can help learn for its users. However, in the market, educational applications still have less attractive elements and features. So, this study aims to develop applications with the theme of education by utilizing the UX Design and Gamification approach. This approach aims to make users more interested and in accordance with user needs. The case study used in this research is English grammar because this knowledge is an important knowledge base that must be possessed by everyone. The test is carried out on users who are students because they are respondents who are in accordance with the grammar level. The test results show that the NPS value given has an average of 59%. This indicates that the application has been accepted by the user. So that by developing this application, it is hoped that it can help users in learning English grammar interactively.